Misrepresentation and capital structure: Quantifying the impact on corporate debt value - Zhou, Xinghua; Reesor, R. Mark (Journal of Corporate Finance, 2015)
Securities class actions typically involve some misrepresentation by a firm that overstates its true value. In securities class actions econometric models are used to assess damages to shareholders. However, studies on measuring damages for debt-holders are limited. Using structural models and leveraging the relationship between equity and firm value, we use observable equity information to determine firm and debt values and hence the effect of misrepresentation on corporate debt values. We find that the misrepresentation impact on debt value depends on the debt's credit risk. Generally, the debt for higher-leverage firms is more sensitive to the misrepresentation impact than for lower-leverage firms and junior debt is more affected by fraud than senior debt. Our proposed methodology allows for debt damages assessments consistent with standard methods for assessing equity damages. Our findings have important consequences for damages assessment and the allocation of settlement awards in securities class actions. In some jurisdictions damages awarded are net of any hedge or risk-limitation transaction. Since corporate securities such as bonds and stocks are often held in portfolios for hedging purposes, measuring the effect of misrepresentation on all of the firm's issuances is essential to accurately computed damages awards. Additionally our approach provides a consistent methodology for computing damages for securities that do not trade on public markets. A case study of a recent securities class action illustrates our methodology.